Social and Cultural Aspects of the Iban Community in Sarawak - Md.Nazri, Haslinda (Idealogy Journal, 2018)
Sarawak is the largest country in the Malaysian Federation, having a rich and colorful cultural heritage from the  diversity of customs and traditions of its multi-ethnic population. Culture is a comprehensive value system consisting of various material and immaterial aspects. Culture needs to be documented to maintain the nation's cultural heritage so that it is not forgotten or lost. Even though they have achieved independence and lives in modernization, the clash between various forms of traditional culture and the new cultural values persists. However, the traditional cultural values must be preserved as the nation's cultural heritage. Keywords: heritage, clash of cultural values, traditional values